Atividade antimicrobiana do óleo essencial de camomila romana (Chamaemelum nobile) - Barbosa, Marcelo Pires (2019)
The increased prevalence of infections by multiresistant microorganisms has drawn the attention of the scientific community to the need for new antimicrobial drugs. At the same time, the perception of the inevitability of the development of resistance to these agents led to a search for alternative methods to treat infections, such as the use of agents without direct antimicrobial activity, but capable of preventing the expression of virulence factors and potentializing the action of antimicrobials. Secondary plant metabolites are rich in biologically active molecules and have become the subject of intense research in this area. The present study aimed to evaluate such activity in the essential oil of Chamaemelum nobile, popularly known as Roman chamomile. The components of the oil were identified by GC-FID and GC-MS, the antimicrobial activity was evaluated by broth microdilution and by antimicrobial synergism test with amikacin. Inhibition of virulence factors were verified with tests of inhibition of biofilm formation, inhibition of motility and interference in the quorum sensing system through the inhibition test of violacein production. The analyzed oil presented α-pinene and β- pinene as major components and a weak antimicrobial action against some strains of Pseudomonas aeruginosa, Acinetobacter baumannii, Shigella sp. and Staphylococcus sp. with MICs of 455 and 227 mg/mL. Oil concentrations of 14,2 and 7,1 mg/mL were able to inhibit the production of violacein in Chromobacterium violaceum and concentrations of 227 and 113 mg/mL inhibited the swarming and twitching types of motility, but induced an increase in biofilm formation in P. aeruginosa PA01. The oil showed strong modulatory activity of the amicacin activity in P. aeruginosa PA01 reducing the MIC for this antimicrobial by 128-fold.